KARAWITAN JAWA SEBAGAI MEDIA BELAJAR DAN MEDIA KOMUNIKASI SOSIAL - Arya Dani Setyawan (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2017)
Karawitan is one of the performances that has developed and been culturally entrenched in the areas of Indonesia, especially in Java, and even it has developed in foreign countries. Karawitan is a medium generated from some elements of the gamelan instruments coveringÂ  sound aesthetics and presentation aesthetics. The unity of the musical elements in karawitan constitutes a paradigm for the manifestation of life, nature, and the environment. The social function of presenting a gendhing in Javanese karawitan is the method applied by society, ranging from the religious characters and aspects, families, to individuals.Karawitan can be narrowed down as a medium of education, which can be seen from the viewpoint of how to play it; karawitan becomes a musical presentation enoyable to listen to when played together. This reflects that togetherness is one thing that is very important to achieve quality music (musical arrangement). This also means moral education in order that we live in togetherness through cooperation, tolerance, empathy, self-adjustment, well-founded dispute not unfounded dispute, and avoidance of selfishness and being individualistic.